Gallium Coordination Polymers Based on Bis‐pyridylethylene Containing Neutral and Cationic 1D Chains and 2D Networks - Schäfer, Thomas; Müller‐Buschbaum, Klaus (Zeitschrift für anorganische und allgemeine Chemie (1950), 2018)
Two new coordination polymers constituted by gallium trichloride and 1,2‐bis(4‐pyridyl)ethylene (bpe) were synthesized. Reactions by the solvent‐free melt‐synthesis approach lead to the unusual formation of multiple cationic coordination polymers containing one‐dimensional chains 1∞[GaCl2(bpe)3]+ and two‐dimensional networks 2∞[Ga2Cl4(bpe)5]2+ in one compound of the formula 2∞[Ga2Cl4(bpe)5]1∞[GaCl2(bpe)3]2[GaCl4]4·3bpe. Reactions under solvothermal conditions in benzene lead to the formation of a neutral one‐dimensional coordination polymer 1∞[GaCl3(bpe)]. Both coordination polymers were characterized by SCXRD, PXRD, simultaneous DTA/TG, elemental analysis, and IR spectroscopy.